APLIKASI PENCATATAN PENERIMAAN PIUTANG BERBASIS ANDROID DENGAN FITUR PEMBERITAHUAN OTOMATIS PADA CV SINAR TERANG FASTENER - Nada, Nasywa Qotri (LPKIA, 2025)
This study aims to develop an Android-based Accounts Receivable Recording Application with an automatic notification feature for CV Sinar Terang Fastener. The company’s main issue is that the recording and monitoring of non-sales customer receivables are still done manually, which poses a risk of delayed collections and disrupts cash flow. The proposed solution is an AppSheet-based application integrated with Google Sheets, designed to simplify the recording, monitoring, and reporting of receivables in real-time while providing automatic notifications before or on the due date. The development method used is the Waterfall model, consisting of requirement analysis, design, implementation, testing, and maintenance phases. The application includes features such as receivable data input, calculation of days until due date, periodic reports, and integrated notifications via email and Android devices. The implementation results show improved work efficiency, easier mobile data access, and reduced risk of missed collections. Thus, this application is considered a practical, efficient, and flexible solution for managing receivables at CV Sinar Terang Fastener and has the potential to be adapted by other companies with similar needs.